Efek Analgetik Ekstrak Daun Gatal (Laportea decumana Roxb. Wedd) pada Mencit Jantan (Mus Muscullus L.) yang Diinduksi Asam Asetat: Penelitian Hewan Coba - Margaret Bambungan, Yulinda; Lerebulan, Exaudian Flourens (Health Information : Jurnal Penelitian, 2023)
Laportea decumana (Roxb.) Wedd, commonly known as "daun gatal" in Papua, is a plant that is empirically used as a pain reliever. The purpose of this study was to determine the analgesic effect and effective dose of L. decumana leaf extract on male mice. The experimental research method was conducted on 25 male mice that were divided into 5 groups according to treatment, which were negative control of 1% Na-CMC, positive control of 1% aspirin, and L. decumana leaf extract doses of 250 mg/kgBW, 500 mg/kgBW, and 1000 mg/kgBW. The results showed that L. decumana leaf extract doses of 250mg, 500mg, 1000mg/kgBW had analgesic effects (0.000<0.05), and the most effective dose was 1000mg/kgBW. Further research is needed to confirm the specific chemical constituents of L. decumana leaf extract as an analgesic.